2015
DOI: 10.1097/yic.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized placebo-controlled trial of adjunctive aripiprazole for chronic PTSD in US military Veterans resistant to antidepressant treatment

Abstract: Many individuals with post-traumatic stress disorder (PTSD) experience persistent symptoms despite pharmacological treatment with antidepressants. Several open-label monotherapy and adjunctive studies have suggested that aripiprazole (a second-generation antipsychotic) may have clinical utility in PTSD. However, there have been no randomized placebo-controlled trials of aripiprazole use for PTSD. We thus conducted a pilot randomized controlled trial of adjunctive aripiprazole versus placebo among Veterans with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Three studies replicated data from other included studies, leaving 55 total studies. Interventions that met inclusion criteria and number of studies using them included aripiprazole (1), [30] brofaromine (2), [31,32] bupropion (1), [33] TF-CBT (2), [23,24,34] citalopram (1), [35] CPT (1), [36] divalproex (2), [37,38] EMDR (2), [39,40] fluoxetine (5), [25,26,[41][42][43][44] guanfacine (2), [45,46] IPT (1), [47] mirtazapine (1), [16] nefazodone (1), [48] olanzapine (3), [18,49,50] paroxetine (7), [51][52][53][54][55][56][57] PE with cognitive restructuring (PE/CR) (2), [58,59] PE (7), [40,47,[58][59][60][61][62] prazosin…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies replicated data from other included studies, leaving 55 total studies. Interventions that met inclusion criteria and number of studies using them included aripiprazole (1), [30] brofaromine (2), [31,32] bupropion (1), [33] TF-CBT (2), [23,24,34] citalopram (1), [35] CPT (1), [36] divalproex (2), [37,38] EMDR (2), [39,40] fluoxetine (5), [25,26,[41][42][43][44] guanfacine (2), [45,46] IPT (1), [47] mirtazapine (1), [16] nefazodone (1), [48] olanzapine (3), [18,49,50] paroxetine (7), [51][52][53][54][55][56][57] PE with cognitive restructuring (PE/CR) (2), [58,59] PE (7), [40,47,[58][59][60][61][62] prazosin…”
Section: Resultsmentioning
confidence: 99%
“…Most medication studies and several psychotherapy studies reported outcome data selectively or in a misleading manner. Examples included partial/nonstandard reporting between text and charts, [19, 20, 22-27, 32-35, 37-39, 42, 44-46, 49, 52, 56, 58, 60, 62, 63, 65-69] switching between mean/mean change, [25, 26, 38, 43-45, 48, 50, 52, 66, 69, 71-75] switching be-tween standard deviations(SD)/confidence intervals/standard errors, [25,26,28,30,43,44,51,55,62,64,67,71,72] omitting baseline outcome data, [28,33,68] omitting variance measures completely, [28,31,68] omitting outcome measures at specific time points, [28,40,68] creation of nonstandard outcome measures by combining standard measures with other variables, [25,28,32,41,44,51,73] splitting outcome measures into subscales without providing total score, [39,58] failure to cross-reference data spread over several publications, [25,26,43,44] and including nonscaled graphs without providing corresponding means. [28,40,68] Data abstraction for most medication studies required mathematical conversion of provided data into mean total CAPS/SPRINT/PSS-I and SD.…”
Section: Quality and Risk Of Biasmentioning
confidence: 99%
“…Randomized 30 participants. Also see Table A2 for baseline analyses informing this trial. To recruit a target population for intervention study Naylor et al, 2015 Proof-of-concept randomized controlled trial of adjunctive aripiprazole in Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF) era veterans with PTSD resistant to antidepressant treatment. Randomized 16 participants. To recruit a target population for intervention study Other Brown, Strauss, et al, 2014 Compared 68 subjects with PTSD and 60 trauma-exposed non-PTSD controls.…”
Section: Table A1mentioning
confidence: 99%
“…This class of drugs exerts lower side effects compared to older antagonists. Aripiprazole was tested among military personnel as adjunctive therapy, if anti- depressants were ineffective [ 91 , 92 ]. The outcomes of these studies have been positive regarding reduction of overall symptoms and safety, but have to be supported by further studies with larger numbers of participants and placebo controls.…”
Section: Studies On Genetic Polymorphisms Among Military Personnelmentioning
confidence: 99%